Representações do Brasil em textos do exame Celpe-Bras - Lima, Ronaldo Amorim (2008)
This study focuses on the representations of Brazil and the Brazilian people portrayed in 230 texts of the individual part of the Portuguese as a Foreign Language (PFL) Proficiency Exam CELP-Bras. For this purpose, it draws on Social Representation Theories, Van Dijk s Critical Discourse Analysis as well as DaMatta s and Almeida s anthropological Studies. After collecting the data and elaborating a framework of themes and topics for the categorization of the analyzed texts, a deeper understanding of the representations of Brazil and the Brazilian People was sought, comparing them to those found in questionnaires previously applied to PFL learners of several different nationalities, aiming at finding instances of divergence and convergence. It was concluded that the texts selected as prompts for the individual part of the exam show the developed and modern side of our society whereas the representations found in the PFL learners compositions still reflect the image portrayed by the means of communication, that is to say, the stereotyped image of Brazil as, mainly, home to soccer, carnival, beautiful nature, and hospitable people.